Fintech and its impact on the economy of Uzbekistan - Khattabov Ubaidullo Botirovich (Academia One Publishing, 2024)
The use of mobile banking, investment and cryptography determines the freedom and new financial technologies that will certainly change the rules of financial services. Customers across the World have already taken this new form of banking. Uzbekistan is also trying to introduce Fintech in Finance, Asset management, Payment and others. This paper studies the important role of Fintech and its evolution. In addition it includes some negative effects that may occur because of Fintech. Moreover it concludes that in the development of Fintech in Uzbekistan, the major objectives are to have a detailed regulation and appropriate security system
Keywords: Fintech; Banking; Finance; Uzbekistan